Integrating Experiential Learning, Distance Education, and Extension Curricularization in an Undergraduate Systems Analysis and Development Program - Araújo, Allysson Allex; Viana, Davi; Kalinowski, Marcos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
Experiential learning is a well-established pedagogical approach that enhances student engagement and skill development through direct application. While widely adopted in in-person education, its integration into distance education remains underexplored, particularly in software engineering extension programs. This experience report investigates student perceptions of an experiential learning-based extension project within a distance education setting, specifically in a Systems Analysis and Development undergraduate program in Brazil. Using a mixed-methods approach, we analyzed student perceptions (from questionnaires and final reports) and the coordinating professor’s reflective observations. Our findings reveal that experiential learning in distance education fosters both technical proficiency (e.g., software development practices and agile methodologies) and professional identity formation (e.g., teamwork, communication, and project management skills). However, challenges such as balancing autonomy and guidance, remote collaboration barriers, and time management struggles emerged as obstacles. Our study contributes by offering actionable lessons for integrating experiential learning into software engineering distance education through the curricularization of extension.